Cobalt protoporphyrin promotes human keratinocyte migration under hyperglycemic conditions - Peng-Hsiang Fang; Ying-Ying Lai; Chih-Ling Chen; Hsin-Yu Wang; Ya-Ning Chang; Yung-Chang Lin; Yu-Ting Yan; Cheng-Hung Lai; Bill Cheng (BMC, 2022)
Abstract Background Complete healing of diabetic wounds continues to be a clinically unmet need. Although robust therapies such as stem cell therapy and growth factor treatment are clinically applied, these treatments are costly for most diabetic wound patients. Therefore, a cheaper alternative is needed. Cobalt protoporphyrin (CoPP) has recently been demonstrated to promote tissue regeneration. In this study, the therapeutic benefits of CoPP in diabetic wound healing were examined. Methods An in vitro wound healing model that mimics re-epithelialization was established to examine the effect of CoPP on the migratory capability of human keratinocytes (HaCaT) in either normal glucose (NG) or high glucose (HG) media, as well as in the presence of either H2O2 or lipopolysaccharide (LPS). At the end of the migration assays, cells were collected and subjected to Western blotting analysis and immunostaining. Results HaCaT were found to migrate significantly more slowly in the HG media compared to the NG media. CoPP treatment was found to enhance cell migration in HG media, but was found to decrease cell migration and proliferation when HaCaT were cultured in NG media. CoPP treatment induced high levels of expression of Nrf-2/HO-1 and FoxO1 in HaCaT cultured in either glucose concentration, although the FoxO1 expression was found to be significantly higher in HaCaT that underwent the migration assay in NG media compared to those in HG media. The higher level of FoxO1 expression seen in CoPP-treated HaCaT cultured in NG media resulted in upregulation of CCL20 and downregulation of TGFβ1. In contrast, HaCaT migrated in HG media were found to have high levels of expression of TGFβ1, and low levels of expression of CCL20. Interestingly, in the presence of H2O2, CoPP-pretreated HaCaT cultured in either NG or HG media had similar expression level of Nrf-2/HO-1 and FoxO1 to each other. Moreover, the anti-apoptotic effect of CoPP pretreatment was noticed in HaCaT cultured in either glucose concentration. Additionally, CoPP pretreatment was shown to promote tight junction formation in HaCaT suffering from LPS-induced damage. Conclusions CoPP enhances cell migratory capacity under hyperglycemic conditions, and protects cells from oxidative and LPS-induced cellular damage in HG media containing either H2O2 or LPS.